Clinical Characteristics of Breast Cancer Patient: A Retrospective Analysis - Shrestha, Samir; Shah, Surendra; Shah, Jay N (Journal of General Practice and Emergency Medicine of Nepal, 2014)
Introduction: Patients with breast cancer have long been thought to have poorer prognosis. It is the 2nd commonest cancer in women in Nepal. The aim of this retrospective study was to conduct a review of data of patients who underwent treatment at Patan Academy of Health Sciences(PAHS) to ascertain the clinico-epidemiological pattern.Methods: The case report of all patients diagnosed to have breast cancer were examined for age, risk factors, symptoms and clinical findings, site of primary tumor and extent of disease, operative management & histopathological results.Results: Among 50 cases, all were females(100%). Mean age of presentation was 42yrs. Main presentation was breast lump, among them 20(40%) had pain and 6(12%) had nipple discharge & 16(32%) had ipsilateral axillary lump. Mean duration of symptoms was 4 months. Mean size of tumor was 4x5 cm an main location was upper outer quardant ( 32.4%). Overlying skin was involved in 22(44%) and chest wall fixation was seen in 16(32%). Out of 50 case, 38(76%) received adjuvant treatment. Fourteen patient with locally advanced breast cancer received neoadjuvant chemotherapy first. Histopathologically infiltrating ductal carcinoma was seen in 94%, medullary carcinoma in 3%, lobular carcinoma in 2%, lymphoma in 1%.Conclusion: In our study, breast carcinoma was prevalent in younger age group commonly in middle class population. Most patients who presented in locally advanced stage were due to lack of awareness and inadequate health care services. Complete treatment was relatively unsuccessful because of poor follow up.